Pembuatan Logo sebagai Identitas Visual UMKM Nasi Padang Ampera One sebagai Upaya Meningkatkan Daya Tarik Konsumen - Novi Fitri Hermati; Cahyadi Abdullah Fikri; Rizki Dwi Maulana; Ilham Mustafa (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This study discusses the importance of creating a logo as a visual identity for Micro, Small, and Medium Enterprises (MSMEs) in increasing consumer appeal. A strong visual identity can strengthen brand image and differentiate MSME products from their competitors. Through a graphic design and visual communication approach, the logo is designed based on business characteristics and target market preferences. The results of the study show that a strategically designed logo can increase consumer trust, strengthen brand image, and provide added value to the product. Creating a logo as a visual identity has proven to be an effective step in supporting MSME marketing in a more professional and attractive way.